Plan de marketing para la exportación del charichuelo al mercado estadounidense, Iquitos 2021 - Panduro Casique, Yolanda del Carmen (2023)
The general objective of this research was to design a marketing plan for the export of Charichuelo to the US market, Iquitos 2021, being an applied study with a descriptive design, the population and sample consisted of 8 studies dealing with export to the market. American and the charichuelo, the instrument that was used a bibliographic card. Given this, the work reached the following conclusions: a marketing plan has been designed according to the internal and external situational analysis from the city of Iquitos. Likewise, it has been determined that the city of Iquitos is one of the places with the greatest diversity of edible native fruit trees in the Amazon, since the charichuelo is a fruit widely consumed by local residents, but it has not yet been possible to expand to other markets. since the companies have not carried out a study to find a target segment, having the opportunity to enter other markets, especially the United States. On the other hand, the strengths, weaknesses, threats and opportunities have been identified, being the charichuelo a fruit that contains magnesium, iron, copper and zinc, important for people's consumption. In addition, it has been possible to establish marketing activities for the export of Charichuelo to the US market, in which a schedule has been established over a period of one year, which will be executed.